Institutional investors, political connection and audit quality in Malaysia - Abdul Wahab, Effiezal Aswadi; Zain, M.; James, K.; Haron, H. (Emerald, 2009)
Purpose – The purpose of this paper is to extend the audit pricing literature by examining whetherinstitutional investors and political connection are associated with higher audit fees.Design/methodology/approach – Both descriptive and multivariate analyses are employed toaddress the research objectives. In addition, the authors use panel data to control for bothheterocedasticity and contemporaneous correlations in each cross-section.Findings – Based on a panel analysis of 390 Malaysian firms from 1999 to 2003, a positiverelationship between institutional ownership and audit fees is found, although the economic impact isminimal. Further, the authors find that audit fees are higher for politically connected firms.Research limitations/implications – A thorough examination on the role of political connection ismuch warranted to provide a better understanding on such connection influences the audit market.Originality/value – This paper provides an alternative view on the role of political connection, andon how they influence the audit market